Effect of Chlorella supplementation on cardiovascular risk factors: A meta-analysis of randomized controlled trials - Fallah, Aziz A.; Sarmast, Elham; Habibian Dehkordi, Saied; Engardeh, Javad; Mahmoodnia, Leila; Khaledifar, Arsalan; Jafari, Tina (Clinical nutrition (Edinburgh, Scotland), 2018)
The effect of Chlorella supplementation on cardiovascular risk factors of subjects with different health status has not been conclusively studied. Therefore, the efficacy of Chlorella supplementation on cardiovascular risk factors was assessed through a meta-analysis. A literature search on five electronic databases was performed and related randomized controlled trials (RCTs) published until 15 January 2017 were identified. For each study, the effect size of each outcome was presented as Un-standardized mean difference and 95% confidence interval (CI). The overall effect for each outcome was calculated using random effects model. Meta-analysis on 19 RCTs with 797 subjects indicated that Chlorella administration significantly decreased the levels of total cholesterol (TC; −9.09 mg/dl, 95% CI: −12.91 to −5.26, P < 0.001), low-density lipoprotein cholesterol (LDL-C; −8.32 mg/dl, 95% CI: −12.22 to −4.42, P < 0.001), systolic blood pressure (SBP; −4.51 mmHg, 95% CI: −6.53 to −2.48, P < 0.001), diastolic blood pressure (DBP, −1.64 mmHg, 95% CI: −3.28 to −0.01, P = 0.049), and fasting blood glucose (FBG; −4.23 mg/dl, 95% CI: −8.29 to −0.17, P = 0.041) whereas changes in triglycerides (TG; 1.73 mg/dl, 95% CI: −7.25 to 10.70, P = 0.706), high-density lipoprotein cholesterol (HDL-C; 1.54 mg/dl, 95% CI: −2.40 to 5.48, P = 0.443), and body mass index (BMI; −0.23 kg/m2, 95% CI: −0.97 to 0.51, P = 0.545) was not statistically significant. Subgroup analyses based on intervention duration and Chlorella doses revealed that administration of Chlorella for 8 weeks or higher and doses higher than 4 g/day significantly reduced TC, LDL-C, SBP, and DBP levels in the participants. Moreover, Chlorella supplementation significantly reduced TC and LDL-C levels in unhealthy individuals, and also reduced SBP and DBP in hypertensive ones. The results indicated that Chlorella supplementation improved levels of TC, LDL-C, SBP, DBP, and FBG but the changes in TG, HDL-C, and BMI were not satisfactory. More precise RCTs on subjects with different health status is recommended to clarify the effect of Chlorella supplementation on cardiovascular risk factors.